La enseñanza de los modelos sobre la naturaleza de la luz - Beléndez, A.; Pascual, I.; Rosado, L. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
Contemporary ideas on science learning is useful to avoid the failure of traditional teaching related to preconcepts or conceptual errors in both students and teachers. In this context the student is introduced to the study of light through the knowledge of the different models or theories which explain the phenomena of light. The different teaching levels are born in mind so as to follow a process of both conceptual and methodological change.